2015
DOI: 10.1080/17429145.2015.1020024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of methyl salicylate on the induction of direct and indirect plant defense mechanisms in poplar (Populus×euramericana‘Nanlin 895’)

Abstract: The objective of this study was to investigate the effect of different concentrations of methyl salicylate (MeSA) on direct defense and indirect defense in poplar cuttings (Populus × euramericana 'Nanlin 895'). Four defense-related enzyme activities, such as superoxide dismutase (SOD, EC1.15.1.1), oxydoreductases peroxidase (POD, EC1.11.1.7), catalase (CAT, EC1.11.1.6), and polyphenol oxidase (PPO, EC 1.14.18.1), were measured. The results showed that the SOD activities were induced by 1.0 and 10.0 mM MeSA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 50 publications
2
18
0
1
Order By: Relevance
“…In our study, disease development in tomato fruit caused by B. cinerea was effectively suppressed by MeSA treatment alone. The results were similar to previous studies which found that application of MeSA could inhibit some diseases in some postharvest products . Moreover, we found that combined MeSA+1‐MCP treatment was more effective in controlling fruit gray mold caused by B. cinerea than MeSA treatment alone.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, disease development in tomato fruit caused by B. cinerea was effectively suppressed by MeSA treatment alone. The results were similar to previous studies which found that application of MeSA could inhibit some diseases in some postharvest products . Moreover, we found that combined MeSA+1‐MCP treatment was more effective in controlling fruit gray mold caused by B. cinerea than MeSA treatment alone.…”
Section: Discussionsupporting
confidence: 91%
“…Salicylic acid (SA), a simple phenolic compound, plays an important role in the development of systemic acquired resistance in different plant tissues . Methyl salicylate (MeSA), a volatile organic compound of the signal transduction pathway, is synthesized from SA and activates the plant defense response . Many studies showed that postharvest treatment with SA or MeSA at appropriate concentrations could enhance resistance to pathogens in postharvest fruits and vegetables such as tomato, mango, jujube, sweet cherry and pomegranate .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lower activity levels of enzymes, such as POD and GR, could explain why Q. libani tended to accumulate much more H 2 O 2 under stress. In fact, both oak species modulate the activities of various enzymes such as CAT, SOD and POD which are the major components of the plant defense mechanisms against pathogens (Tang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Methyl salicylate (MeSA) is a volatile organic compound which is synthesized from SA. MeSA is associated with induced resistance plant defense which has been used in effective disease control methods 28 29 30 .…”
mentioning
confidence: 99%